An accurate C0 finite element model of moderately thick and deep laminated doubly curved shell considering cross sectional warping. (September 2015) - Thakur, Sandipan Nath; Ray, Chaitali
Abstract: A C 0 finite element model based on the higher order shear deformation theory has been developed for moderately thick and deep doubly curved laminated composite shells of various shapes. The new accurate equations of elastic deformation by incorporating cross sectional warping of the laminated shells have been developed. The present finite element model has been developed by using eight noded isoparametric shell element with nine degrees of freedom per node. The numerical analysis of laminated shells using the present model has been carried out under sinusoidal loading. The present formulation has been validated by comparing the results in terms of deflection and stresses for moderately thick and deep shells with those obtained from the three dimensional elasticity solution. Highlights: C 0 FEM models with HSDT are developed for moderately deep thick laminated shell. Model 1 is developed considering z/R term in strain components. Model 2 is developed neglecting z/R term in the strain components. Results of both models are compared to study the effect of z/R in the static analysis. Results shows model 1 is more suitable for moderately deep thick laminated shell.